Effects of Ascorbic Acid Supplementation on Lipid Peroxidation and Glutathione Levels in Exhaustive Physical Exercise - ATALAY GUZEL, NEVIN; COSKUN, SULE; GONUL, BILGE; BALABANLI, BARBAROS (Asian Journal of Chemistry, 2010)
The purpose of this study was to examine the effects of exhaustive physical exercises on lipid peroxidation in blood, liver and skeletal muscle and also to assess the effect of ascorbic acid on the differentiation in antioxidant mechanism in rats. For this purpose rats were divided into four groups; control, exhaustive exercise, ascorbic acid supplementation + exhaustive exercise and ascorbic acid supplementation. Exercised rats were run on a rodent treadmill at a speed of 27 m/min at % 15 grades. Average exhaustion time was determined as 55 min. Ascorbic acid was administered 20 mg/kg/d i.p. for 45 d prior to exercise. Thiobarbituric acid reactive substance, glutathione and ascorbic acid amounts were measured by spectrophotometer. As a result of this study, statistical significance of changes were observed in thiobarbituric acid reactive substance amounts in liver and plasma; glutathione levels in muscle and plasma and ascorbic acid amounts in liver especially in the group in which ascorbic acid was supplemented. The fact that the ascorbic acid supplement was performed in exhaustive physical exercises comprised the different responses in the distinct tissues due to the antioxidant effects. On the other hand ascorbic acid supplementation without exercise played an oxidant role in different tissues.